Correlation Between Aftereffects for Roughness of Surfaces of Metal Counterface and Carbon-Plastics - Sirenko, H.O.; Skladanyuk, M.B.; Soltys, L.M. (Physics and Chemistry of Solid State, 2015)
Regularities of change of isotropic roughness surfaces of steel 45 in friction and wear in a pair with polymer composite has been researched. It has been detected that the topography of the conjugated metal surface with polymer composite is the dominant factor in determining the value of wear of carbon-plastics at both the start and in the process friction and wear when the metal surface roughness is created by the composite. It has been established that between aftereffects values for roughness of metal counterface and polymer composite in friction and wear exists reliable linear relationship.